PENGEMBANGAN MODEL REDUKSI RESIKO DAN KALASI KINERJA PEMBIAYAAN MUDHARABAH PADA LEMBAGA KEUANGAN MIKRO SYARI’AH - Siti Maria Wardayati; Nining Ika Wahyuni; Nur Hisamuddin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
The development of Islamic financial institutions in Indonesia is very fast eventhough it is a new institution that all products are new in this Muslim-majoritycountry. This study will test the competence variables account syariah officer andrisk of financing in relation to the financing is affecting performance, and will alsotest the variable business ethics and information asymmetry in relation to risk andfinancial performance. Sample of this research is Islamic Microfinance Institutionsin Jember and Bondowoso with respondent managers and leaders Sharia Microfinance Institutions using primary data obtained through questionnaires. This studyused a quantitative approach and the data processing using Partial Least Square(PLS). Final output of this research is the development of arisk reduction model offinancing is an attempte scalation of financing performance.